Effects and characteristics of the implementation of the 1921 agrarian reform in Iaşi county - Sebastian Doboş (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
The historiographical and socio-economic topic of the 1918-1921 agrarian reform, marked by a considerable degree of difficulty due to a multitude of objective, quantitative as well as qualitative factors, represents a point of reference in the research endeavours focused on the social and economic evolution of Romania. In fact, the major difficulties in the scientific approaches dedicated to the reform initiated by decree in 1918 are inherently determined by the statistical and historical sources, the causes being the stages of registration, sampling, centralization and processing processes, as well as the material and personnel resources which were very limited at that time. The issue of statistical and economic data volume deficiencies can be easily observed upon consulting archived documents, which contain numerous modifications, alterations and other interventions, researchers encountering real difficulties in extracting data and exploiting their real potential. The effects of the 1921 agrarian reform on the evolution of the interwar society of Iasi County were overall multiple and complex, influencing to a greater or lesser degree all spheres of activity: economy, politics, culture, a.s.o. Substantial changes in the agricultural property structure following the implementation of the agrarian reform resulted in the small peasant household as a basic economic unit in the primary sector of Iasi County. The inter-war agricultural censuses corroborated with the statistics compiled by the authorities show that land ownership in Iasi county underwent substantial changes, compared to the situation prior to the year 1918
Keywords: N00; N30; N50; 330; agricultural sciences; economic history; historiography; interdisciplinarity; rural economy